Philosophy bites again - Edmonds, David (O. U. P, 2014)
Philosophy Bites Again is a brand new selection of interviews from the popular podcast of the same name. It offers engaging and thought-provoking conversations with leading philosophers on a selection of major philosophical issues that affect our lives. Their subjects include pleasure, pain, and humour; consciousness and the self; free will, responsibility, and punishment; the meaning of life and the afterlife. Everyone will find ideas in this book to fascinate, provoke, and inspire them.